KONSISTENSI PENILAIAN DALAM MELAKSANAKAN PEMBELAJARAN DI PAUD - Khulusinniyah Khulusinniyah (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2022)
Carrying out an assessment is one of the teacher's obligations in carrying out a series of learning. Even in PAUD, assessment becomes an obligation for teachers to find out the extent of child development and the success of the stimulation carried out by the teacher. The results of the assessment will then become an evaluation of the learning process carried out, so that the assessment must be truly objective. To achieve the objectivity of an assessment in PAUD, there needs to be consistency in setting indicators, assessment criteria, and learning outcomes, so that children are not disadvantaged, and the follow-up of these assessments can really develop the child's potential optimally.